Capacity Building GERMAS di Desa Tamantirto, Kecamatan Kasihan, Bantul - Fauzi, Ekha Rifki; Widyawarman, Danang; Anugrah, Dena (DHARMA BAKTI, 2021)
Background: the increase in non-communicable diseases (PTM) in the community is one indicator to increase awareness of healthy living habits. PTM cases can be prevented and minimized with the culture of GERMAS (Healthy Community Movement). Objective: improving education and health promotion with capacity building for empowerment of GERMAS. Methods: Intervention with the use of a pocket book “Healthy is GERMAS'' and health promotion posters related to GERMAS. Result: the result is hoped that the community will be more aware of undergoing GERMAS which is proven in their daily lives. In addition, there is an increase in the quality of life that is better in order to avoid non-communicable diseases. Conclusion: this conclusion is that the service can be a reference for health workers or other communities in conducting GERMAS in their environment.